DEVELOPMENT OF ENVIRONMENTAL INSURANCE IN CONDITIONS OF ECONOMIC INSTABILITY - Victoria Borisova; Iryna Samoshkina; Larysa Poliatykina (Baltic Journal of Economic Studies)
The objective of this article is to establish the theoretical and methodological foundations and develop the applied tools for environmental insurance. The research employs a range of methodologies, including dialectical cognition, system and structural analysis, synthesis, integrated approaches, regulatory support, and others. Problem statement. The objective of this study is to elucidate the role of environmental insurance in enhancing environmental safety in the event of accidental environmental pollution. In the case of global disasters, it is challenging to discern whether they have a purely natural or anthropogenic origin. The majority of contemporary disasters are a combination of natural and anthropogenic causes, with the resulting damage being significant and difficult to quantify. In light of these considerations, it becomes evident that environmental insurance assumes a pivotal role in periods of economic turbulence. Methodology. The research is based on the generalisation of the conceptual framework of environmental insurance, the justification of the causes and consequences of the need for environmental risk insurance, and the development of industrial and agricultural production. A regression analysis was conducted on 30 agricultural enterprises, with the parameters of the regression equation determined using a matrix of initial data for correlation and regression analysis of profitability. The results of the study show that accidental environmental pollution due to accidental circumstances causes significant damage. To reduce environmental risks, it is proposed to create a system of environmental insurance, the main prerequisite of which is the principle of cross-border functioning. Results. It has been demonstrated that environmental risk insurance represents a valuable instrument for guaranteeing environmental security. It is evident that in the event of unforeseen circumstances, the potential for significant accidental environmental pollution necessitates the implementation of environmental insurance to ensure the attainment of environmental safety standards for all participants. Practical implication. The findings of the study, including its recommendations, are of practical interest and may be recommended for implementation in the practice of insuring agricultural enterprises against environmental risks. Value / Оriginality. The fundamental premise of environmental insurance for agricultural enterprises is to enhance the existing framework and substantiate the operational mechanism for environmental insurance coverage of their land resources. The potential applications of environmental risk insurance in the context of industrial and agricultural production are explored. In order to assess environmental risks, it is proposed that the most serious threats should first be identified and ranked, and then the environmental risk should be assessed, taking into account factors such as economic damage and mortality. It is demonstrated that in order to effectively evaluate the feasibility of a regional environmental insurance system, it is essential to develop an organisational and economic framework for implementing such a system in the region.